Role of Allama Iqbal Open University in Promoting Education among Rural Women in Southern Punjab - Zafar Masaud (International Islamic University Islamabad, 2018)
The study was designed to investigate the role of Allama Iqbal Open University (AIOU) in promoting education among rural women. The study was conducted in Southern Punjab. The objective of the study was;1) to identify the role of AIOU in promoting education among rural women 2) To evaluate the role of tutors in promoting education among rural women. It was descriptive research in nature and used survey method for data collection. The Population of the study was consisted of 8387 female students and 422 tutors in Bahawalpur and Vehari region. The researcher collected data through simple random sampling technique from 308 female students and 177 tutors. Two separate questionnaires were developed for students and tutors. The collected data was analyzed with frequently used statistical techniques of frequency score, percentage score and mean score. It was found that AIOU is playing an active role in promoting education among rural female students, in facilitates in different academic activities and through different administrative measures. Another finding of the study informed us that tutorial meetings provide opportunities to the female student to interact with their fellow, so that female rural students enhance their education. The study concluded that tutors are playing an active role in tutorial meetings in promoting female education through interaction among female rural students.